ADAPTIVE MANAGEMENT VCT PADA WANITA PEKERJA SEKS DI PUSKESMAS KABUPATEN PEMALANG DALAM SAAT PANDEMI COVID-19 - Nabela Putri Yanuari (JKM (Jurnal Kesehatan Masyarakat) Cendekia Utama, 2022)
The Covid-19 pandemic has disrupted the voluntary counseling and testing (VCT) program for female sex workers (WPS) as evidenced by a decrease in the use of VCT in FSW. Therefore, the existence of COVID-19 requires adaptation to program sustainability (adaptive management). The purpose of this study was to find out adaptive management VCT in female sex workers at the Pemalang District Health Center in the Covid-19 pandemic situation. This type of qualitative research uses the focus group discussion (FGD) method to collect data related to the adaptive VCT on female sex workers at the primary health care in the Covid-19 pandemic situation. Participants involved in the FGDs were stakeholders in the management of the VCT HIV program for female sex workers. Data analysis using content analysis method (content analysis). The results showed that the adaptive carried out is not doing mobile VCT, VCT at the primary health care with health protocols, delivering test results via SMS, not doing post-test counseling. Challenges and obstacles in adapting to VCT at the primary health care are the interest of women sex workers to do VCT at the primary health care still low, the counseling provided is limited, women sex workers do not understand the test results, and the risk of messages being not opened. Design improvements based on ideas and ideas are through health promotion with social media, some from the community of female sex workers being role models, owners (pimps) requiring regular VCT FSW at the primary health care, running mobile VCT (6 months) with a health protocol, counselors must be able to provide information that is easy to understand, clear and concise, can use the telephone to convey test results.